The effect of varied concentration of fragrant pandan leaf extract (Pandanus amaryllifolius Roxb) as a natural larvacide on the mortality of Aedes aegypti instar III mosquito larvae - Deviyani, Dira; Lukiyono, Yauwan Tobing; Anggraini, Rahayu; Andini, Ary (Environmental and Toxicology Management, 2023)
Dengue Hemorrhagic Fever (DHF) is a disease caused by Dengue virus infection. The use of synthetic larvicides causes side effects on human health. Efforts are made to use natural insecticides to minimize contact with dangerous chemical substances. Fragrant pandan leaf plants have secondary metabolite compounds including alkaloids, saponins, flavonoids, tannins and polyphenols, these secondary metabolite compounds can kill larvae. This study aims to determine the effect of variations in the concentration of fragrant pandan leaf extract (P. amaryllifolius Roxb.) on the death of Aedes aegypti Instar III larvae. This type of research is experimental, with a Control Group Post-Test Design. The level of influence of concentration variations is seen from the Lethal Concentration (LC50) and Lethal Time (LT50) values. The data obtained were analyzed using a probit regression test or probit analysis to determine the effect of variations in the concentration of wangi pandan leaf extract (P. amaryllifolius Roxb.) on the death of A. aegypti Instar III larvae. and expressed as Lethal Concentration (LC50) and Lethal Time (LT50) with a confidence level of 95.0%, the probit test obtained the results of LC50-6 hours was 7.770%, LC50-8 hours was 6.516%, LC50-24 hours was 4.409%, LT50-2% is 31,973 hours, LT50-4% is 24,745 hours, and LT50-6% is 16,129 hours, from the parametric tests carried out the results were not  normal and homogeneous, then the Kruskal-Wallis test was continued and showed a P-Value 0,000 (<0,05). So it can be said that there is effect of variations in the concentration of fragrant pandan leaf extract (Pandanus amaryllifolius Roxb.) on the mortality of third instar A. aegypti larvae.